Preliminary Study on Benzoic Acid Adsorption from Crude Active Coals and Bentonite - Abbes Boucheta; Soufi Kacimi; Razika Bared (Aceh International Journal of Science and Technology, 2016)
We studied the adsorption of pollutant benzoic acid by the modified bentonite of Maghnia (west of Algeria), and coal (Coal from the mines, southwest of Algeria, Bechar area) under three forms, crude and activated. Kinetic data show that the balance of bentonite (as amended) adsorbs organic acids better than activated and raw coal. Indeed, the intercalation of bentonite with benzoic acid causes an improvement in the texture of porous material, which allows its use in the adsorption of organic compounds. The adsorption isotherms (Langmuir and Freundlich) indicate that the adsorption of benzoic acid by the coal and bentonite yielded results favorably. The results obtained showed the practical value of using the activated coal and bentonite (as amended) in the field of remediation of water contaminated with organic pollutants